A reciprocidade nos grupos em fusão em Jean – Paul Sartre - Gonçalves, Aline Ibaldo (2017)
The present research will deal with the problem of concrete relations with the other in Jean- Paul Sartre. Specifically, think about the possibility of the salvation of relationships with each other. In Being and Nothingness, concrete human relations were doomed to failure, but our thesis is that in the Critique of Dialectic Reason there is the possibility of overcoming the subject-object relationship through group in fusion. What once was a relationship with the other that resulted in failure, a more practical relationship is now possible where individuals, assuming their free individual praxis, can recognize themselves in a group when there is oppression and domination. Thus, a relation of interiority between individuals is created in which the objectification of the other must be overcome. In this context, there will be a reciprocal relationship with the other mediated by the Third.